Artificial gravity as a countermeasure for mitigating physiological deconditioning during long-duration space missions - Clément, Gilles R.; Bukley, Angelia P.; Paloski, William H. (Frontiers in Systems Neuroscience, 2015)
In spite of the experience gained in human space flight since Yuri Gagarin’s historical flight in 1961, there has yet to be identified a completely effective countermeasure for mitigating the effects of weightlessness on humans. Were astronauts to embark upon a journey to Mars today, the six-month exposure to weightlessness en route would leave them considerably debilitated, even with the implementation of the suite of piece-meal countermeasures currently employed. Continuous or intermittent exposure to simulated gravitational states on board the spacecraft while traveling to and from Mars, also known as artificial gravity, has the potential for enhancing adaptation to Mars gravity and re-adaptation to Earth gravity. Many physiological functions are adversely affected by the weightless environment of spaceflight because they are calibrated for normal, Earth’s gravity. Hence, the concept of artificial gravity is to provide a broad-spectrum replacement for the gravitational forces that naturally occur on the Earth’s surface, thereby avoiding the physiological deconditioning that takes place in weightlessness. Because researchers have long been concerned by the adverse sensorimotor effects that occur in weightlessness as well as in rotating environments, additional study of the complex interactions among sensorimotor and other physiological systems in rotating environments must be undertaken both on Earth and in space before artificial gravity can be implemented.